PENGARUH SUBSITUSI TEPUNG PISANG KEPOK TERHADAP KUALITAS KUE PUTU AYU - Kaputri, Yossy; Gusnita, Wiwik; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research was motivated by thelack utilization of banana flour used in diversity of food processing, while banana flour can be one alternative to replace some of wheat flour as main material from Putu Ayu. This study aims to analyze the effect of substitution treatment of banana flour by 25%, 50%, 75% and 100% on the quality of volume, shape, color, aroma, texture and taste. This type of research is a pure experiment using a completely randomized design method. The data used are primary data sourced from 30 semi-trained panelists by proposing the organoleptic test format. Analyze data using ANAVA, if FCcount> FTable then proceed with Duncan test. From the results of this study there is a significant influence of the use of banana powder on the quality of the cake with the use of pure banana as much as 50% mengahasilkan cake putu ayu with the best quality, including volume (soft), color (light brown), kerstur (soft) , and taste (Banana). Keyword: Banana Flour, Putu Ayu, Quality.